Phase equilibria and liquid phase behavior of the K2O-CaO-SiO2 system for entrained flow biomass gasification. (1st April 2020) - Santoso, Imam; Taskinen, Pekka; Jokilaakso, Ari; Paek, Min-Kyu; Lindberg, Daniel
Abstract: Experimental data of solid-liquid phase equilibria in the K2 O-CaO-SiO2 systems vital for many technologies and industrial applications are very limited and even not available at some primary phase fields. In the present study, by using Equilibration-Quenching-Phase compositional analysis (EPMA/EDS) method, liquidus compositions in equilibrium with pure solid SiO2, CaO·SiO2, 3CaO·2SiO2, 2CaO·SiO2, K2 O·6CaO·4SiO2 and K2 O·2CaO·2SiO2 compounds and 2CaO·SiO2 solid solution were measured. By knowing the evaporation behavior of K2 O during the equilibration process, specific initial mixtures could be selected to obtain liquidus data for targeted final equilibrium assemblages. EPMA and EDS analysis results were compared. The experimental data obtained in the present study were discussed and compared with the results from previous experimental investigations and the assessed ternary phase diagrams. Some novel experimental data of the liquid at single and double solid phase saturations were obtained in the present study and they can be used to correct and support the predictions and thermodynamic assessments of the K2 O-CaO-SiO2 system. Present investigation reports liquidus projections and detailed phase relations among the phases in isothermal sections at 1000, 1100, 1200, 1300 and 1400 °C. Viscosity calculations of the liquid at different compositions between 1000 and 1400 °C also have been made. A combination of phase equilibria study and the viscosity predictions in the present investigation provides suitable temperature and ash composition regions for optimal flow properties of the slag in entrained flow biomass combustion or gasification processes.